Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2020)
A dataset containing 4214750 species occurrences available in GBIF matching the query: { "and" : [ { "or" : [ "BasisOfRecord is Observation", "BasisOfRecord is Machine Observation", "BasisOfRecord is Human Observation" ] }, { "or" : [ "Country is Angola", "Country is Burundi", "Country is Benin", "Country is Burkina Faso", "Country is Botswana", "Country is Central African Republic", "Country is Côte d'Ivoire", "Country is Cameroon", "Country is Congo, Democratic Republic of the", "Country is Congo, Republic of the", "Country is Djibouti", "Country is Algeria", "Country is Egypt", "Country is Eritrea", "Country is Ethiopia", "Country is Gabon", "Country is Ghana", "Country is Guinea", "Country is Guinea-Bissau", "Country is Equatorial Guinea", "Country is Kenya", "Country is Liberia", "Country is Libya", "Country is Lesotho", "Country is Morocco", "Country is Madagascar", "Country is Mali" ] }, "HasCoordinate is true", "HasGeospatialIssue is false" ] } The dataset includes 4214750 records from 396 constituent datasets: 78 records from Etude d'état initial de la biodiversité dans le cadre des EIES sur les plateaux situés dans la zone sud (Sorontorè) de la concession minière de Guinea Alumina Corporation(GAC) dans la region de Boké (CESP2016-022). 122 records from Inventory of plant species in the municipal forests of Nonsinasson, Gbede, Pele, Toukou, Fita, Wogbo, Bobe (Benin, West Africa). 1348 records from Inventory of Wari maro forest (Benin). 6247 records from Census of medical plant species of Benin (West Africa) by SOS Biodiversity. 198 records from Tortue Olivâtre. Données publiées dans le cadre du projet JRS Bénin. 1214 records from Continuous Plankton Recorder Dataset (SAHFOS). 7032 records from Agents pathogènes responsables de maladies traitées à l'Hôpital de Mènontin (Cotonou, Sud-Bénin). 15276 records from Organisms responsible of infectious diseases listed at Menontin District Hospital (Cotonou, Atlantic department, South-Benin). 1053 records from Reef Life Survey: Global reef fish dataset. 42979 records from The census of national forest of Benin .. 1268 records from Makira. 884 records from Diversité et distribution de quelques espèces de plantes agroforestières au Bénin. 124 records from Birds of Grand Kru Liberia. 3 records from F.M.Ghazzawi (1938) Plankton of the Egyptian waters. Two Cladocera from the plankton. Notes and Memories of the Hydrobiology and Fisheries Directorate of Egypt, Notes and Memories No 31. 12 records from Report on the Danish Oceanographical Expeditions 1908-10 to the Mediterranean and adjacent seas- Calcareous Algae. 14 records from Distribution of Pheronema species from the N.E. Atlantic and the Mediterranean. 56 records from SuLaMa Amblyomma chabaudi occurence data. 26 records from Bivalvia distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 6214 records from Diversité et distribution des espèces de plantes menacées au Bénin. 68 records from VectorBase (Bioinformatics Resource for Invertebrate Vectors of Human Pathogens). 2329 records from Census of agroforestry plant species of Benin (West Africa) by SOS Biodiversity. 607 records from Inventory of Bassila forest (North-Benin). 377 records from Inventory of Niaouli forest (South-Benin). 183 records from SCAR Biogeographic Atlas of the Southern Ocean - Porifera - Data. 25 records from Recoveries of birds ringed by Revtangen Bird Observatory (Southwest Norway), 1936-2018. 63 records from SuLaMa yam occurence data. 720 records from (Table 6) Distribution of Pleistocene to late Pliocene nannofossils in ODP Hole 108-660A. 86 records from EWT: African Crane Conservation Programme Sightings. 1264 records from Avifauna occurrence data for Arabuko Sokoke Forest in Kenya. 15 records from Sizing Ocean Giants. 291 records from SuLaMa reptile survey 2013. 3 records from Ascidiacea distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 721 records from Forest inventory for above ground carbon estimation in Biosphere Reserve of W.. 576 records from Ecological inventory of Borassus aethiopum (Mart.) populations in the Pendjari Biosphere Reserve, Benin. Data mobilized in the framework of JRS Benin project. 167346 records from Bird tracking - GPS tracking of Lesser Black-backed Gulls and Herring Gulls breeding at the southern North Sea coast. 633 records from Liste d'espèces animales recensées au cours des activités de l'Organisation pour le Développement Durable et la Biodiversité (ODDB ONG) au Bénin. 42 records from Lemur_occurrences_Madagasikara_Voakajy_MLP_20190917. 430 records from Phanérogames recensés aux Monts Nimba. 116 records from SuLaMa plant monitoring. 2307 records from Data on animal species in the Biosphere Reserve of W Bénin. Data mobilized in the framework of JRS Biodiversity Foundation funded project in Benin. 5934 records from Agroforestry species in Parkia biglobosa's parklands in Northern Benin. 22 records from The fishery ground near Alexandria. XVI. Cumacea, stomatopoda, leptostraca by Adolf Steuer (1938).Notes and Memoirs No 26.. 4982 records from (Table 1) Distribution and relative abundance of mid-Cretaceous planktonic foraminifers at DSDP Hole 79-545. 816 records from Espèces végetales sur sable roux du fourré de Ranobe, PK 32 Toliara. 1398 records from Wildmeat consumption by Allebone-Webb 2009 at Equatorial Guinea. 94 records from The fishery ground near Alexandria. XXI. Tanaidacea and Isopoda by H.J. Larwood (1940).Notes and Memoirs No35.. 1 records from pangolin and pangolin products seized by the customs and pangolin public aided record from 2010 to 2019. 8 records from Lamippidae - endoparasites of octocorals of the world. 6146 records from Diversité des espèces menacées des zones classées et terroirs villageois du Bénin (Afrique de l'Ouest).. 365 records from Phytoplankton from Ghana. 41 records from Edaphobase. 14 records from The Vascular Plant Collection at the Botanische Staatssammlung München. 211 records from L’évaluation environnementale du projet de barrage de la retenue d'eau, à Sangaredi (Boké), pour la Société minière Guinea Almuna corporation (CESP2016-022). 12 records from Lepidoptera collection of Hannu Saarenmaa. 8977 records from Evaluation et conservation des espèces forestières de la forêt de Lama (Bénin). 40 records from The University of Melbourne Herbarium. 693 records from The Herpetology Collection at the Staatliches Museum für Naturkunde Stuttgart. 270 records from Australian National Wildlife Collection provider for OZCAM. 138 records from (Figure 1) Stratigraphic distribution of taxa at DSDP Hole 79-547B. 1 records from Asia-Pacific Dataset. 2557 records from Sapo National Park Bio-monitoring Data. 225 records from L’évaluation environnementale du projet du barrage de la retenue d'eau, de Guinea Alumina corporation à sangaredi, Boké (CESP2016-022). 74 records from Etude d'état initial de la biodiversité dans le cadre des EIES sur les plateaux situés dans la zone sud de la concession minière de Guinea Alumina Corporation(GAC) dans la region de Boké (CESP2016-022). 59 records from Research database of Madagascar grasses compiled by Maria Vorontsova. 4378 records from Espèces envahissantes et menacées des pâturages naturels de la zone soudano-guinéenne, données mobilisées dans le cadre du projet BID. 395 records from Biological observations from the Discovery Investigations 1925-1952. 98 records from SuLaMa Microcebus griseorufus occurence data. 441 records from Relevé floristique dans les bassins du fleuve Milo à Kankan (CESP2016-022). 9391 records from Levantamento de Mamíferos do Parque Nacional da Quiçama - INBAC/RWCP - 2017. 4 records from Aplacophora distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 1555 records from Occurrence de vecteurs de maladies recensés à l'Hôpital de Zone Ouidah-Kpomassè-Tori. 2534 records from Elaboration de table de tarif de cubage multispécifique (I). 376 records from (Figure 7) Distribution and character of selected biogenic and lithologic components at DSDP Hole 79-545. 299 records from Insect Collection of the Laboratory of Applied Entomology of the Faculty of Sciences of the University of Lome. 1472 records from Census of plant species in forest gaps in the natural forest of Massi (Lama Forest reserve, South-Benin). 8 records from H.Bachmann (1936) The fishery grounds near Alexandria. XIV. Phytoplankton from the Nile. Fisheries Research Directorate of Egypt, Notes and Memoirs No 22. 1086 records from Vertebrate observation dataset of North and West Africa (CIBIO-Biodeserts). 2416 records from Ecology, structure and dynamics of private plantations of Teck (Tectona grandis Lf) of the Department of the Atlantic (South Benin), 2011. 193 records from Sapo National Park Chimpanzee Survey 2016. 2421 records from Census of plant species in Toffo forest reserve. 295 records from Odonata of the Congo River 2010 expedition. 1972 records from Threatened species recorded in protected areas and riparian land in Sudano-guinean and Sudanian agroecological zones. 4428 records from "Categorization of the wild food plants and their importance for primate development in the natural forest of Akpe (Lama) in southern Benin.". 34 records from Etude d'état initial de la biodiversité dans le cadre des EIES sur les plateaux situés dans la zone (Wossou) sud de la concession minière de Guinea Alumina Corporation(GAC) dans la region de Boké (CESP2016-022). 1668 records from Finnish Bird Ringing and Recovery Database. 440 records from (Figure 5) Distribution and relative abundances of microbiota recovered from the Jurassic section of DSDP Hole 79-547B. 5 records from published Chenopodium vulvaria observations. 49688 records from Southern African Bird Atlas Project. 4054 records from Dados de ocorrência de espécies da flora da Guiné-Bissau. 4040 records from Planetary Biodiversity Inventory Eumycetozoan Databank. 16059 records from CSIC-Real Jardín Botánico-Anthos. Sistema de Información de las Plantas de España. 2654 records from Patrols activities and fixed transect data collections of the fauna of the W biosphere reserve of Benin of 2017. 2246 records from Plants censued in the framework of the follow up of the dynamics of the secondary forests of the Lama forest reserve (Southern Benin). 39 records from Amaranthaceae Observations Tanzania and Kenia. 428 records from (Figure 8) Distribution and character of selected biogenic and lithologic components at DSDP Hole 79-547A. 1937 records from Vegetable Germplasm Occurrence. 10000 records from Evaluation de la dynamique de la flore aquatique au Bénin en association avec les espèces envahissantes Pistia stratioides et Eichhornia crassipes. Data mobilized in the framework of JRS Biodiversity Foundation funded project. 561 records from Taxon occurrence data for the FungalRoot database. 152 records from Inventory of plant species in plantations in Benin. 57 records from SOMBASE – Southern Ocean mollusc database: a tool for biogeographic analysis in diversity and evolution. 2739 records from Ringing Data of Birds of Arabuko-Sokoke Forest. 3782 records from (Table 3) Distribution of Cretaceous nannofossils at DSDP Hole 79-547A. 4932 records from Census of the threatened species of Benin.. 2911 records from Change in aboveground biomass carbon stock following the establishment of exclosures on degraded lands in Tigray, Ethiopia. 3444 records from (Table 2) Distribution of Cretaceous nannofossils at DSDP Hole 79-545. 5381 records from (Figure 1) Distribution of dinoflagellate cysts in the mid-Cretaceous of DSDP Hole 79-545. 200 records from National census of Lepidochelys olivacea (Benin). 4601 records from (Table 2) Distribution and relative abundance of mid-Cretaceous planktonic foraminifers at DSDP Site 79-547A. 1292 records from Census of tapia forest plant species in central highland of Madagascar. 770 records from F.M.Ghazzawi (1939) Plankton of the Egyptian waters. A study of the Suez Canal Plankton. Notes and Memories of the Hydrobiology and Fisheries Directorate of Egypt, No 24. (A) The Phytoplankton. Preliminary Report. 499 records from EBCC Atlas of European Breeding Birds. 9257 records from Plan Aménagement et de Gestion Simplifié (PAGS) des forèts sacrées des départements de l'Ouémé-Plateau et le Collines. Données mobilisées dans le cadre du projet JRS Bénin. 553 records from Occurrence records of southern African aquatic biodiversity. 260 records from SuLaMa reptile survey II 2012. 3939 records from Census of plant species in Pahou forest reserve. 280 records from Liberian Greenbul Expedition 2013. 103 records from Avifauna do Parque Nacional da Quiçama. 399 records from Gola National Park Biomonitoring Data. 3633 records from Census of medicinal and agroforestry plants of Benin. 44 records from Espèces menacées de la Guinée forestière extraites dans la base de données de CRRA Sérédou Macenta, IRAG (BID-AF2015-0066-REG). 14145 records from Occurrence of plant species in the proposed Ankasa-Bia-Krokosua ecological corridor of Ghana. 179 records from NMNH Extant Specimen Records. 74 records from SuLaMa reptile monitoring. 13 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 1081 records from Riparian Vegetation Survey of Lower Okavango Delta by Ringrose and Matherson 1999. 76 records from Questagame weekly feed. 9 records from Syllidae (Polychaeta) from the North Mediterranean Coast of Egypt. 186 records from Monitoring the dynamics of a medicinal tree species Haematostaphis barteri Hook. F. in Benin. 299 records from List of animal species censused during activities of ODDB NGO in Benin. 6029 records from Inventaire des espèces végétales dans le cadre de plusieurs études menées au Sud-Bénin. 7 records from Distribution of Aphrocallistes beatrix in the N. Atlantic. 26 records from Liste des oiseaux de BZM Belambo. 10000 records from List of animalia, fungi and plant species recorded through naturalist observations and research activities in Benin. Data mobilized in the framework of a JRS Biodiversity Foundation project of Benin. 2 records from MVZ Herp Observations (Arctos). 655 records from Data collected on animal species through census using Kilometric Abundance Index (KAI) in Biosphere Reserve of W-Bénin. Data mobilized in the framework of JRS Biodiversity Foundation funded project in Benin. 395 records from Plant species occurrences recorded from selected sites in the mid Tana River Basin, Kenya. 2 records from National Whale and Dolphin Sightings and Strandings Database. 3008 records from Inventaire et dénombrement des oiseaux du Parc Naturel Communautaire de la Vallée du Sitatunga (Sud Bénin). 65205 records from BirdMap Data - GPS tracking of Storks, Cranes and birds of prey, breeding in Northern and Eastern Europe. 5938 records from Plan Aménagement et de Gestion Simplifié (PAGS) des forêts galeries des départements de l'Ouémé-Plateau. Data mobilized in the framework of a JRS Biodiversity Foundation project in Benin. 6652 records from Inventory of plant species through Benin (West Africa). 258 records from Systematic census of the private plantations of the firewood of the Benin .. 896 records from Data on agroforestry plant species of Benin. 212 records from Meise Botanic Garden Herbarium (BR). 1 records from Non Fish Species Occurrence in ASEAN Region. 9 records from Steinbock (1937) Turbellaria XIV. The fishery grounds near Alexandria. Notes and Memories of the Fisheries Directorate of Egypt, No. 25. 241 records from Living collections at Aburi Botanic Gardens in Ghana. 43 records from FBIP:IZIKO-UCT:Historical Invertebrates (1930-1980). 564 records from Atewa Range Forest Reserve Bryophytes dataset, Ghana. 12 records from University of Vienna, Institute for Botany - Herbarium WU. 20 records from KTP Ring Data. 1755 records from Long Term Time-Series Data on Fish Monitoring by Okavango Research Institute, Botswana. 1 records from In situ observations of Stygiomedusa gigantea. 2812 records from (Figure 4) Distribution of dinoflagellate cysts in the Albian/Cenomanian of DSDP Hole 79-547A. 16 records from SuLaMa blind cave fish occurence data. 366 records from Inventaires des adventices dans les bas-fonds rizicoles de Sérédou (CESP16-0022-Guinea). 324 records from Marine Mammal Observation - Total E&P Angola 2006-2011. 32 records from srli_global_araneae. 10138 records from Diversity and distribution of multipurpose species in Benin. 6 records from Corvids Literature Database. 2107985 records from EOD - eBird Observation Dataset. 1759 records from Census of birds species of Benin from the inventory data in National Park of Pendjari. 1 records from Museum of Comparative Zoology, Harvard University. 1893 records from Collection of occurrence data on animal species in the Biosphere Reserve of Pendjari in 2001, 2004, and 2013.. 6537 records from Lemur_occurrences_TAF_MLP_20190917. 71 records from Pathogènes responsables des maladies à potentiel épidémiologique recensées à l'Hôpital de Zone Ouidah-Kpomassè-Tori. 412 records from Gregarous Benin valuable species. 1477 records from Inventaire des espèces végétales productives dans les Systèmes Agro-forestiers aux alentours de la Forêt classée de Ziama en Guinée Forestière (BID-AF2015-0066-REG). 3320 records from (Figure 4) Distribution and relative abundances of the benthic foraminifers recovered from the Jurassic section of DSDP Hole 79-547B. 16 records from ZFMK DORSA. 11018 records from observe_tuna_bycatch_ecoscope. 150 records from Report on the Danish Oceanographical expeditions 1908-1910 to the Mediterranean and adjacent seas - Pelagic Polychaetes. 2344 records from Species composition of protected areas and riparian land in Sudano-guinean and Sudanian agroecological zones. Data mobilized in the framework of JRS Biodiversity Foundation project. 1208 records from Point Count Data of Birds of Arabuko-Sokoke Forest (2009 - 2010). 753 records from Hexacorallians of the world. 1910 records from observe_tuna_ecoscope. 181 records from Inventory of natural and agroforestry stands characterized by Xylopia aethiopica (Dunal) A. Rich. (south-Benin). 2536 records from Invasive Alien Species Occurrence in Ghana. 150 records from IUCN Red List assessment occurrence data for freshwater species native to the Lake Malawi/Nyasa/Niassa Catchment. 277 records from Rwanda's wetlands biodiversity data from different inventories that were conducted between year 2008 and 2017. 2360 records from Inventaire et dénombrement des oiseaux du Parc Naturel Communautaire de la Vallée du Sitatunga (Sud Bénin). 13 records from Espèces envahissantes de la Guinée forestière extraites dans la base de données de CRRA Sérédou Macenta, IRAG.. 1547 records from Diversité et distribution de quelques espèces de plantes médicinales au Bénin. 14 records from Data from EIAs and other studies coordinated by the national forestry authority of Uganda. 16 records from PROJET DE CONSTRUCTION D’UNE ROUTE DE TRANSPORT DES MINERAIS DE BAUXITE DE GAC: EIES, inventaire des amphibiens (CESP2016-022). 40 records from Syllidae, Magelonidae and Maldanidae from the Northwestern Coast of Egypt. 40 records from SuLaMa Galidictis grandidieri occurence data. 118 records from JRS Wetands data Rwanda, 2019. 1 records from Antarctic Amphipod Crustaceans: Ant'Phipoda Database (BIANZO). 3325 records from Distribution de quelques espèces de plantes et de Mimusops andongensis au Bénin. 1 records from Faun. 7300 records from Macaulay Library Audio and Video Collection. 4853 records from Inventaire des espèces végétales du sous bois des plantations de Teck de la forêt naturelle de la Lama. 310 records from The Fishery Grounds near Alexandria.VII.Decapoda.By Heinrich Balss.(1936).Notes and memoirs No. 15. 2072 records from Inventaire et dénombrement des oiseaux du Parc Naturel Communautaire de la Vallée du Sitatunga au Sud Bénin. 43420 records from Plant Diversity and Distribution on the Continental Cameroon Mountains. 411 records from SuLaMa reptile survey I 2012. 25 records from Distribution of bat roosts in the interior of Arabuko-Sokoke Forest and adjacent farmlands in Gede, Kilifi County, Kenya. 2 records from Portuguese Seaweeds. 70 records from Etude d'état initial de la biodiversité dans le cadre des EIES sur les plateaux situés dans la zone sud (Horèwendou) de la concession minière de Guinea Alumina Corporation(GAC) dans la region de Boké (CESP2016-022). 6 records from Norwegian Species Observation Service. 202 records from Liberia National Pygmy Hippo Action Plan Data. 89632 records from Kenya Bird Map Occurrence Data. 32 records from Billards A. 1936.The fishery grounds near Alexandria. VI Hydroidea. Notes et memoires No 13. 600 records from Occurrence data of Birds of the Upper Tana Basin, Kenya. 4840 records from Elaboration du tarif de cubage multispécifique. 5413 records from Distribution and abundance of different bat species in the interior of Arabuko-Sokoke Forest and adjacent farmlands in Gede, Kilifi County, Kenya. 16382 records from Ethnobotanique et diversité floristique des écosystèmes temporairement inondés et fragiles du Bénin. 91 records from Etude d'état initial de la biodiversité dans le cadre des EIES sur les plateaux situés dans la zone sud (Petoun kolonie) de la concession minière de Guinea Alumina Corporation(GAC) dans la region de Boké (CESP2016-022). 55 records from Amphibian and Reptile species occurrence records in the Tana River Basin, Kenya. 102 records from Liste des plantes médicinales utilisées dans la préfecture de Labé et observées sur le terrain.. 661 records from Etude floristique de la forêt marécageuse de Lokoli au Bénin. 1339 records from Inventory of Bassila, Pénéssoulou, Wari maro, Djigbé, Lama and Bonou forests (Benin). 3 records from BioFokus. 630 records from Relevé floristique dans les bassins du fleuve Niger à Faranah (BID-AF2015-0066-REG). 78 records from Anymals+plants - Citizen Science Data. 252 records from Mammifères: Etude d'état initial de la biodiversité dans la concession minière de Guinea Alumina Corporation(GAC) dans la region de Boké (CESP2016-022). 1535 records from Collection of Occurrence data on mammal species during wildlife census in W Biosphere Reserve in 2013 and 2015.. 65 records from Borror Lab of Bioacoustics (BLB), Ohio State University. 4 records from SharkBase. 339 records from Deep Atlantic Bivalves. 11861 records from Xeno-canto - Bird sounds from around the world. 8693 records from Aranzadi Ringing Scheme (bird ring-recovery data). 583 records from Invasive plant species recorded in protected areas and riparian land in Sudano-guinean and Sudanian agroecological zones of Benin. 2 records from Pittsburg State University, Theodore M. Sperry Herbarium. 10343 records from Study of the floristic diversity of some habitats of Cercopithecus erythrogaster erythrogaster, the red-bellied monkey in South Benin. 420 records from Biological observations from the Dana Expedition Reports. 11 records from BANDAPHO, BAse de DAtos sobre Aphodiidae. 165 records from Mortensen Th. And Steuer Ad. 1937. The fishery grounds near Alexandria. XIII Echinoderma. Notes and Memoirs No 21. Hydrobiology and Fisheries Directorate, Egypt. 454 records from Hatikka Observation Database. 160114 records from Fishbase. 1 records from Togo National Herbarium Database. 32 records from New records for a catalogue of Chalcididae (Hymenoptera, Chalcidoidea) from Morocco. 2500 records from Aves of wetlands and protected forests in Benin. 683 records from Lama Forest reserve Inventory, South Benin. Data published in the framework of JRS Benin project. 1275 records from (Fig. 12) Distribution of dinoflagellate cysts in Early Cretaceous sediments of DSDP Hole 50-416A in the North Atlantic. 60 records from Steuer Ad., 1939. The fishery grounds near Alexandria. XVIII Sipunculoidea, Phoronidea, Brachiopoda, Enteropneusta and Acrania. Notes and Memoirs No. 30. Fouad I Institute of Hydrobioloy and Fisheries, Egypt. 128 records from (Figure 3) Foraminiferal assemblages recovered from DSDP Hole 79-547B. 3039 records from Diveboard - Scuba diving citizen science observations. 65 records from PlutoF platform observations. 29559 records from Occurrences de vecteurs de maladies recensées à l'Hôpital de Mènontin. 3 records from Asteroidea distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 2629 records from Data on medicinal plants of Benin. 180 records from (Table 7) Distribution of the large, few-chambered Globigerinelloides species in DSDP Hole 79-545. 9210 records from SuLaMa bird occurence data. 7508 records from Kenya Wildlife Service, Laikipia Samburu Aerial Census, 2008. 38 records from Harant H. 1939. The fishery grounds near Alexandria. Ascidiacea (Cartes 1-5). Notes et Memoirs No 28.. 6610 records from Biodiversité végétale de quelques écosystèmes au Bénin. 820 records from Indian Ocean Islands - Historic Freshwater Insect Taxa. 17 records from New contributions to the Eulophidae fauna from Morocco (Hymenoptera: Chalcidoidea) with comparison in the North African region. 1521 records from Les plantes forestières utiles en Guinée Forestière. Inventaire des espèces et usages (BID-AF2015-0066-REG). 1205 records from Ecology, structure and dynamics of private plantations of Teak (Tectona grandis Lf) of the Department of the Atlantic (South Benin), 2011. 718 records from Bird species occurrences recorded from selected sites in mid Tana River Basin, Kenya. 1127 records from Census of the secondary forests of the Lama forest reserve (Southern Benin). 152 records from Etude d'état initial de la biodiversité dans le cadre des EIES sur les plateaux situés dans la zone sud (Poutèrè tinguilinta) de la concession minière de Guinea Alumina Corporation(GAC) dans la region de Boké (CESP2016-022). 920 records from Annotated list of observed birds in W and Pendjari Reserves in Benin, February 2010. 1 records from Biogeographic distribution of Antarctic and sub-Antarctic Cumacea. 426 records from Species composition in twelve (12) Afzelia africana Sm & Pers populations in Benin.. 739 records from List of medicinal and agroforestry plants found in various ecosystems of Benin. 99 records from Coleoptera of Togo: data of the LEA Insect Collection of the University of Lome. 1699 records from Census of plant species in Monts-Kouffè regions, center Benin. 182 records from Polychaete Study in Northeastern Mediterranean Coast of Egypt. 3681 records from Plantes médicinales et agrofrestières inventoriées au cours de l'élaboration du plan Aménagement et de Gestion Simplifié (PAGS) des forêts galeries des départements de l'Ouémé-Plateau.. 130 records from Data from ILAM surveys conducted by ARCOS in Bugesera landscape for year 2017. 157375 records from FLOTROP, a massive contribution to plant diversity data for open ecosystems in Tropical Africa.. 6368 records from Boro and Xudum Floodplain Vegetation Data 2007. 87 records from Additional list of gregarous Benin valuable species. 201 records from TilapiaMap. 7703 records from Diversité des plantes des parcours naturels et des forêts au Bénin. 232 records from Census of waterbird in Benin Flyway. 5327 records from Kenya Virtual Museum Records. 97 records from Birds and plants of Firestone Harbel Plantation. 969 records from (Fig. 11) Distribution of dinoflagellate cysts in Early Cretaceous sediments of DSDP Hole 41-370 in the North Atlantic. 17584 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 6131 records from Evaluation de la dynamique des espèces envahissantes (Pistia stratioides et Eichhornia crassipes) et de la flore aquatique au Bénin. 251384 records from Kenya Birdmap (Full protocol records). 79 records from Etude d'état initial de la biodiversité dans le cadre des EIES sur les plateaux situés dans la zone sud (Pompo) de la concession minière de Guinea Alumina Corporation(GAC) dans la region de Boké (CESP2016-022). 393 records from Census of invasive alien and threatened species plants of Benin. 8 records from The fishery ground near Alexandria. XX. Nemertini by Herman Friedrich (1940).Notes and Memoirs No 38.. 2228 records from Point count data of Birds of Arabuko-Sokoke Forest (2017). 6759 records from Inventaire faunique dans le cadre de l'Etude socio-économique de référence des possibilités de valorisation durable des produits forestiers non ligneux dans les réserves de faune de la pendjari. 31 records from BoBO - Botanic Garden and Botanical Museum Berlin Observations. 1 records from Brachiopoda distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 180 records from (Table 7) Distribution of the large, many-chambered Globigerinelloides species in DSDP Hole 79-545. 32883 records from naturgucker. 94 records from Animal Sound Archive. 4508 records from Contribution à la gestion durable des forêts : Caractéristiques écologiques et structurales de la forêt naturelle d’Akpè (Lama) au Sud du Bénin.. 437 records from Zooplankton from selected sites in Ghana. 83 records from Etude d'état initial de la biodiversité dans le cadre des EIES sur les plateaux situés dans la zone sud de la concession minière de Guinea Alumina Corporation(GAC) dans la region de Boké (CESP2016-022). 98925 records from iNaturalist Research-grade Observations. 3083 records from Medicinial plant species found in protected areas and riparian lands in Sudano-guinean and Sudanian agroecological zones. Data mobilized in the framework of BID National project BID-AF2015-0065-NAC and funded by EU. 3886 records from Plant species occurrences recorded from selected sites in the upper Tana River Basin, Kenya. 62 records from Etude d'état initial de la biodiversité dans le cadre des EIES sur les plateaux situés dans la zone sud (Sindiarè) de la concession minière de Guinea Alumina Corporation(GAC) dans la region de Boké (CESP2016-022). 11847 records from Census of plant species of Benin (West Africa): Database4. 24 records from Inventory of plant species produced in CERF nuseries. 37 records from Plant Species Recorded at Elluokrom in Ghana. 180 records from (Table 6) Abundance distribution of the 'clavate' subspecies of the genus Globigerinelloides in DSDP Hole 79-545. 810 records from (Table 1) Distribution of ostracods in Jurassic sediments of DSDP Hole 79-547. 36 records from BIOLOGICAL SCIENCES DATA. 2661 records from "Répertoire des Forêts sacrées dans les Départements de l’Ouémé t du Plateau. Data mobilized in the framework of BID National project BID-AF2015-0065-NAC and funded by EU. 816 records from (Table 7) Distribution of Pleistocene to Miocene nannofossils in ODP Hole 108-661A. 213 records from Occurrence records of small and medium sized mammal species in Tana River Basin, Kenya. 258 records from Stem volume and biomass development in Lama Forest reserve, South Benin. Data published in the framework of JRS Benin project. 127 records from Inventory of Bonou, Kilibo and Lama forests (South and centre Benin). 1679 records from Tree characteristics and vegetation structure in the interior of Arabuko-Sokoke Forest and adjacent farmlands in Gede, Kilifi County, Kenya. 54944 records from SAFRING: Historical Bird Ringing Records (2005-2009). 36 records from Check list of waterbirds at Wadi Djedi in Ziban Oasis-Algeria. 30954 records from CABI Africa Invasive and Alien Species data. 106 records from Etude d'état initial de la biodiversité dans le cadre des EIES sur les plateaux situés dans la zone sud (Thiankoye) de la concession minière de Guinea Alumina Corporation(GAC) dans la region de Boké (CESP2016-022). 280 records from Collections and observation data National Museum of Natural History Luxembourg. 12 records from Polychaeta from the Eastern Harbour of Alexandria. 3531 records from Coordinated Waterbird Counts. 900 records from Fishes of Ghana. 1 records from Colección de referencia de otolitos, Instituto de Ciencias del Mar-CSIC. 86 records from Occurrence of Butterfly species recorded in Western and Brong Ahafo Regions of Ghana. 2787 records from A Rocha Kenya bird ringing data from Arabuko-Sokoke Forest and Gede Ruins Forest, Kenya, 2019. 1460 records from Census of invasive alien plant species of Benin (West Africa) by SOS Biodiversity. 569 records from Spatial repartition of Antiaris toxicaria Lesch., Ceiba pentandra (L) Gaert, Terminalia superba Engl. & Diels and Triplochyton scleroxylon K. Schum. in Niaouli, Bonou, Pobe forests (South-Benin). 2510 records from Kenya Wildlife Service, Laikipia Samburu Aerial Census, 2012. 8 records from Cirripedia distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 498 records from Inventory Pobè forest in South East of Benin. 189 records from Chas.H. O'Donoghue, D.Sc. & Dora de Watteville,M.A. The fishery grounds near Alexandria. XX-Bryozoa. Notes and Memoirs No 34. Hydrobiology and Fisheries Directorate, Egypt.. 6 records from Crinoidea distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 1 records from Flora of tanzania. 1515 records from Mosquito Occurrence Dataset. 16065 records from Inventaire botanique et étude ethnobotanique des espèces végétales du Jardin Botanique de l'Institut de Recherche Agronomique de Guinée (BID-AF2015-0066-REG). 26699 records from Southern African Bird Atlas Project 2. 1599 records from Inventaire des bois par espèce végétale de la forêt classée de Ziama en Guinée Forestière (BID-AF2015-0066-REG). 122 records from M. Burton (1936). The Fishery grounds near Alexandria IX – Sponges. Notes and Memoirs No.17. Department of Zoology, British Museum. Fisheries Research Directorate. Ministry of Commerce and Industry, Egypt.. 7552 records from PPEAO - Pêches scientifiques. Peuplements de poissons des écosystèmes estuariens, lagunaires et continentaux d'Afrique de l'Ouest. 437 records from (Table 7) Distribution of Maestrichtian to late Campanian nannofossils in ODP Hole 108-661A. 259 records from Copepod crustaceans identified by Prof. Arthur G. Humes. 959 records from (Table 7) Distribution of planktonic foraminifers in ODP Hole 108-660A. 1078 records from (Table 8) Distribution of planktonic foraminifers in ODP Hole 108-661A. 72 records from Guinée Ecologie, 2015, Etude d'état initial de la biodiversité dans le cadre des EIES sur les plateaux situés dans la zone sud (Loppè Tambougura) de la concession minière de Guinea Alumina Corporation(GAC) dans la region de Boké (CESP2016-022). 23212 records from Bird tracking - GPS tracking of Western Marsh Harriers breeding near the Belgium-Netherlands border. 68 records from UCT: Southern African Butterfly Conservation Assessment (1815-2009). 21618 records from African Plants - a photo guide. 303 records from Fauvel P. 1937. The fishery grounds near Alexandria. XI.Annelida Polychaeta. Notes et memoires No 19. 13 records from ECNASAP - East Coast North America Strategic Assessment. 2 records from Danish Mycological Society, fungal records database. 1768 records from Ground Census Data for Lake Nakuru and Nairobi National Parks. 4294 records from Census of animal species in Biosphere Reserve of Pendjari. Data mobilzed in the framework of JRS Biodiversity Foundation funded project in Benin. 506 records from Inventory of Dogo-Kétou forest (South-Benin). Data mobilized in the framework of JRS Biodiversity Foundation project. 1836 records from Inventaire et dénombrement des oiseaux du Parc Naturel Communautaire de la Vallée du Sitatunga (Sud Bénin) (suite1). 16664 records from Vegetation assessment and forest dynamic study of various areas in Gabon from 2000 to 2018. 1661 records from Inventaire des plantes alimentaires au Bénin. 4195 records from Kalahari woody vegetation Transect by Ringrose and Matheson (1995 - 2009). 75 records from Phytoplankton in longitudinal east-west transect of the Mediterranean Sea,1999.. 5625 records from Plant inventory of W Biosphere reserve (North-Benin). Data mobilized in the framework of JRS Biodiversity Foundation project. 17 records from Broch H. 1935. The fishery grounds near Alexandria. III Cirripeds. Notes et Memoires No 10.. 1418 records from Floodplain and aquatic vegetation survey, Okavango Panhandle, 2004. 2674 records from Inventaire des espèces animales présentes dans les aires protégées et parcs nationaux au Bénin. 6 records from Echinoidea distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 1916 records from Plant Species Sampled in Some Selected Forest Reserves in the High Forest Zone of Ghana. 107 records from The Spider Collection at the Staatliches Museum für Naturkunde Stuttgart. 588 records from Agroforestry plant species found in protected areas and riparian lands in Sudano-guinean and Sudanian agroecological zones. Data mobilized in the framework of BID National project BID-AF2015-0065-NAC and funded by EU. 3 records from UCT: Southern African Reptile Conservation Assessment (1910-2009). 651 records from NaGISA Project. 4 records from Dr.Karl Viets. 1935. The fishery grounds near Alexandria. IV. -Some Marine Mites From Alexandria. Notes and Memoirs No 11. Fisheries Research Directorate, Egypt.. 2017 records from Flore des reliques forestières de la commune de Dangbo. 436 records from List of plant species inventoried through Benin (West Africa). 133 records from Schellenberg A. 1936. The fishery grounds near Alexandria. Amphipoda Benthonica. Notes and memoirs No 18.. 976 records from Global Lacustrine Diatoms. 5074 records from Census of medicinal plants of Benin.. 812 records from Census of secondary forest of Itchèdè-Toffo (Southern Benin). 6514 records from Diversité et distribution des plantes envahissantes au Bénin. 333 records from Indian Ocean Islands - Historic Freshwater Diatom Data. 208 records from Inventory of Synsepalum dulcificum Daniell in south Benin. Data mobilized in the framework of BID National project BID-AF2015-0065-NAC and funded by EU. 69 records from Etude d'état initial de la biodiversité dans le cadre des EIES sur les plateaux situés dans la zone sud (Kérémara) de la concession minière de Guinea Alumina Corporation(GAC) dans la region de Boké (CESP2016-022). 101 records from Report on the Danish Oceanographical Expeditions 1908-1910 to the Mediterranean and adjacent seas- Engraulidae-Clupeidae. 10 records from Vatova A., 1935. The fishery grounds near Alexandria, II. A bottom sample taken at Alexandria, Notes and Memoirs No 9. Fisheries Research Directorate, Egypt. 915 records from Spatial distribution of a threatened multi-use species Afzelia africana Sm & Pers in Benin (West- Africa). 390 records from Inventory of Penessoulou forest (North West Benin). 935 records from Occurrence records of mammal species in Tana River Basin, Kenya. 3919 records from ecoscope_observation_database. 9902 records from Data collected in the framework of the accomplishment of research activities. 3 records from ALA species sightings and OzAtlas. 417 records from Surveys of the East Coast Akalat, Sheppardia gunningi, in Arabuko-Sokoke Forest, 2005-2011. 882 records from Steuer A. 1939. The fishery grounds near Alexandria. XIX Mollusca. Notes and Memoirs No 33. 3203 records from Biodiversity assessment in the Yangambi Biosphere Reserve. 1154 records from Palmiers sauvages du Bénin. 31078 records from West African Vegetation Database. 808 records from Census of living organisms for infectious, parasitics and virals diseases recorded in the Departemental University Hospital Center of Ouémé-Plateau, South-Benin. Database 2. 1426 records from Bassins versants de vere et nalon (BID-AF2015-0066-REG). 20430 records from Distribution de quelques espèces de plantes agroforestières et médicinales au Bénin. 1216 records from "Répertoire des Forêts sacrées dans les Départements de l’Ouémé et du Plateau. Data mobilized in the framework of JRS Biodiversity Foundation project. 1884 records from Recensement de quelques vecteurs de maladies du Bénin (Afrique de l'Ouest). 37863 records from Plants of Ghana. 2264 records from Carnet en Ligne. 243 records from L’évaluation environnementale du projet du barrage de la retenue d'eau, de Guinea Alumina corporation à sangaredi, Boké (CESP2016-022). 532 records from Inventory of Bonou and Itchèdè forests in south east of Benin. 885 records from (Figure 3) Distribution of dinoflagellate cysts in the late Albian of DSDP Hole 79-547B. 8 records from MEL AVH data. 1476 records from African Mammalia. 231 records from L’étude d’impact environnemental et social(EIES) pour le projet de GAC de construire d'une route de 16 km au sud de la concession de Tinguilinta dans la région de Boké, Guinée (CESP2016-022). Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences